Real-Time Burst Localization in Complex Water Transmission Lines Using Hydraulic Gradient Analysis - Taegon Ko; Raziyeh Farmani; Edward Keedwell; Xi Wan (Engineering Proceedings)
This study introduces a methodology for the real-time detection and localization of bursts in water transmission lines by comparing estimated and measured Hydraulic Gradient (HG) values across pipe segments. Employing a deep learning approach, the method analyzes the complex relationships between system states such as flows, HGs, pump and valve operations. The approach capitalizes on the difference in HG values before and after a burst, enabling precise burst localization. Tested on a real incident, the method proved effective in accurately identifying burst locations, offering a practical solution for operators.